Rancang Bangun Sistem Pendukung Keputusan Pemilihan Supplier pada PT AMSI dengan Metode Promethee - Halim, Agus Wijanarko; Sudarmaningtyas, Pantjawati; Mastan, Ignatius Adrian (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2014)
The selection of the supplier is a very important because it can affect performance in fulfilling the raw materials. Supplier selection process at PT Makmur Sentosa Alindo International (AMSI) is done only by checking the prices of goods at the cheapest per supplier and the availability of goods, so that the quality of raw materials and the accuracy of the number of orders that are not purchased in accordance with the desired. PT AMSI should be more careful in their purchases of raw materials. PT AMSI require additional criteria such as the accuracy of the number of orders and the quality of raw materials in the raw material supplier selection thus obtained as expected. PT AMSI requires a decision support system that generates suggestions or recommendations based on the results of supplier selection criteria condition or expected. Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE) is a method of decision-making by many criteria. With the supplier selection decision support system capable of generating suggestions or recommendations based on the results of supplier selection criteria desired condition.